Instructor led rotational model: An innovative approach to social work practicums in hospital environments - Dube, Kealey; Grant, Stephanie; Fulton, Amy; Judge-Stasiak, Angela; Oiffer, Andrea (My University, 2024)
With the saturation of student practicum placements requests in urban centres, job vacancies, budgetary restraints, and social workers’ intensive workloads, field education coordination teams are increasingly challenged to find social workers who are able to supervise student practicums and secure educational partnerships with organizations willing to support their staff in doing so. This is especially true in hospital settings, where social workers are still feeling the effects of the Coronavirus (COVID-19) pandemic in their daily work lives. Hospital practicums are highly sought out by social work students and yet there are few practicum opportunities for students compared to the demand. Social workers are employed in various practice settings, including hospital social work. As social workers are Canada's largest group of mental health professionals within the hospital system, having robust and sustainable practicum opportunities is critical to the training and development of future social workers. To address these ongoing challenges in social work field education, the University of Calgary, MacEwan University, and Alberta Health Services worked together to develop and pilot a new practicum model at the Bachelor of Social Work level. This practicum model, titled the ‘Instructor Led Rotational Model’, was implemented as a pilot project during the winter 2023 semester. This article provides an overview of this initiative, including a description of innovative practice education components and discussion of the challenges in field education that the model aims to address. Considerations for revisions and future offerings of the instructor led practicum model are also identified.
Keywords: instructor led; field education; social work; rotational model; healthcare